The Influence of Patient Safety Competence on Patient Safety Activities and Nurse Performance Assessment at Mardi Waluyo Regional Hospital, Blitar City - Yuda Dwi Prasetyo; Agusta Dian Ellina; Ratna Wardani (Lembaga Pengembangan Kinerja Dosen, 2025)
Hospital is a health service place that provides services based on safety competency and safety activities that are evaluated using performance assessment. The purpose of this study was to determine the effect of patient safety competency on patient safety activities and nurse performance assessment. The independent variable in this study is patient safety competency, nurse performance assessment is the dependent variable while patient safety activity is the mediating variable. The study used an observational analytical design with a cross-sectional approach. Respondents in the study were some nurses at Mardi Waluyo Hospital, Blitar City who had a patient safety competency certificate totaling 159 respondents. The sampling technique used simple random sampling. The results of the regression analysis obtained a significant effect on patient safety competency on patient safety activities and nurse performance assessment with ap value = 0.01. The variable that has a dominant influence is safety competency with a standardized coefficient of 0.327 compared to safety activities in patients with a standardized coefficient of 0.312. The conclusion in this study is that there is an effect of patient safety competency on patient safety activities and nurse performance assessment. The results of the study are in line with previous research and theories which show that patient safety competency has a greater influence on nurse performance assessments directly compared to the presence of patient safety activities as a mediating variable, but it is possible that other factors play a role in the differences in the effects of influence between variables. Hospital policies, safety culture, and the level of awareness of the work team in implementing daily safety practices may play a role in the difference in influencing effects between variables. However, it is also possible that there are other factors such as the attitude and motivation to work of individuals who are considered not to meet the expectations of the leadership.